Individual and Combined Anatomic Risk Factors for the Development of an Anterior Cruciate Ligament Rupture in Men: A Multiple Factor Analysis Case-Control Study. Issue 2 (February 2022) - Misir, Abdulhamit; Sayer, Gokhan; Uzun, Erdal; Guney, Betul; Guney, Ahmet
Background: No comparative studies have evaluated anatomic risk factors in a large cohort including both patients with anterior cruciate ligament (ACL) ruptures and healthy participants. Purpose: To determine which anatomic parameters are independently associated with an ACL rupture and the diagnostic values of the individual and combined anatomic parameters. Study Design: Case-control study; Level of evidence, 3. Methods: A total of 352 male patients who underwent arthroscopic ACL reconstruction because of a primary ACL rupture and 350 age-, sex-, body mass index–, and side dominance–matched healthy participants were included. Measurements of 32 previously determined parameters and 7 calculations were performed. Between-group differences were calculated. Univariate and multivariate logistic regression models and receiver operating characteristic curve analysis were conducted for the individual and combined independently associated factors. Results: The mean age and body mass index of all participants were 29.9 ± 7.7 years and 27.2 ± 3.1, respectively. There were significant differences between the groups regarding the notch width (NW), notch shape index, anterior tibial slope, notch width index, NW–eminence width (NW:EW) ratio, notch height, axial lateral wall angle, medial intercondylar ridge thickness, alpha angle, medial tibial depth (MTD), lateral tibial slope (LTS), coronal tibial plateau width, eminence width index, tibial proximal anteroposterior distance (TPAP), lateral condylar anteroposterior distance (LCAP)/TPAP, ACL cross-sectional area, ACL volume, medial and lateral meniscal cartilage height, medial and lateral meniscal cartilage angle (MCA), and medial and lateral meniscal cartilage bone height. The NW:EW ratio (odds ratio [OR], 4.419; P = .017), MTD (OR, 8.617; P = .001), LTS (OR, 2.254; P = .011), LCAP/TPAP (OR, 2.782; P = .037), and medial MCA (OR, 1.318; P = .010) were independently associated with the development of an ACL rupture. Combining the independently associated factors revealed a sensitivity of 93% and a specificity of 94% (area under the curve, 0.968). Conclusion: Patients with ACL ruptures could be distinguished from uninjured controls with high sensitivity and specificity via the combined use of the NW:EW ratio, MTD, LTS, LCAP/TPAP, and medial MCA. In clinical practice, these findings may contribute to the development of preventive strategies for ACL ruptures.